Legal Obedience, Social Change, and Health Issues: Analysis of the Governmental Decree No. 6 of 2012 on Cattle Control at Palu City (Medico Legal Update, 2020)
This paper aims to analyze the factors which cause the violation of the Governmental Decree No. 6 of 2012on Cattle Control at Palu City by cattle owners. This research was conducted at South Palu, especially atthe North Birobuli District using the qualitative-naturalistic method. The results of this research show thatthe society has not yet obeyed the Regional Decree No. 6 of 2012 on Cattle Control at Palu City area dueto some factors: (1) the new values of the Regional Decree No. 6 of 2012 is against the old values of thecattle owners; (2) the cattle owners do not have an understanding of the stipulations which apply nor dothey understand the social change which is currently happening; (3) The attitudes and behaviors of thepoliceofficers and the changemakers were inconsistent and rather discriminative; and (4) the disobediencemay cause health problems which are anthrax, nail and mouth disease, or other diseases to the cattle.